Circadian Clock and Complement Immune System—Complementary Control of Physiology and Pathology? - Shivshankar, Pooja; Fekry, Baharan; Eckel-Mahan, Kristin; Wetsel, Rick A. (Frontiers in Cellular and Infection Microbiology, 2020)
Mammalian species contain an internal circadian (i.e., 24-h) clock that is synchronized to the day and night cycles. Large epidemiological studies, which are supported by carefully controlled studies in numerous species, support the idea that chronic disruption of our circadian cycles results in a number of health issues, including obesity and diabetes, defective immune response, and cancer. Here we focus specifically on the role of the complement immune system and its relationship to the internal circadian clock system. While still an incompletely understood area, there is evidence that dysregulated proinflammatory cytokines, complement factors, and oxidative stress can be induced by circadian disruption and that these may feed back into the oscillator at the level of circadian gene regulation. Such a feedback cycle may contribute to impaired host immune response against pathogenic insults. The complement immune system including its activated anaphylatoxins, C3a and C5a, not only facilitate innate and adaptive immune response in chemotaxis and phagocytosis, but they can also amplify chronic inflammation in the host organism. Consequent development of autoimmune disorders, and metabolic diseases associated with additional environmental insults that activate complement can in severe cases, lead to accelerated tissue dysfunction, fibrosis, and ultimately organ failure. Because several promising complement-targeted therapeutics to block uncontrolled complement activation and treat autoimmune diseases are in various phases of clinical trials, understanding fully the circadian properties of the complement system, and the reciprocal regulation by these two systems could greatly improve patient treatment in the long term.